Physiotherapy Students’ Perspectives of a Blended Learning Approach Through the COVID-19 Pandemic Years - Belcher, S; Larmer, P; Christopherson, R; Sampath, KK (Physiotherapy New Zealand, 2024)
The Waikato Institute of Technology launched an innovative approach in 2019 to deliver a Bachelor of Physiotherapy degree. The programme utilised a blended-block learning andragogy of face-to-face (block-week) and online learning. At the end of the first 4-year cycle, it seemed pertinent to understand the students’ perspective of this approach, while recognising possible effects of the COVID-19 pandemic. An online questionnaire was distributed to a sample of students (n = 70), with 44% completing the survey. Preference to continue with block-week learning was split: 32.2% of students wished to continue with the current approach, 32.2% preferred to discontinue and return to traditional campus teaching, and 35.6% were unsure. Those students who preferred to discontinue predominantly originated or moved to the Hamilton region for study. Students who preferred block-blended learning were often from a population that the programme was meant to serve, living in rural areas and/or having significant family/ community responsibilities, meaning they were unable to move to the institute and would struggle to access the course in any other manner. To reduce fatigue and improve satisfaction, students also suggested mixing content delivery every week, engaging in 2–3 days of face-to-face sessions and 2–3 days online, moving away from block-learning yet retaining blended-learning. Most students believed the course was well positioned to manage the effects of COVID-19; however, they recognised practical skills learning and access to clinical placement experience was reduced. Future research could focus on exploring the benefits and barriers of online learning developed for physiotherapy-specific content.
Keywords: 4201 Allied Health and Rehabilitation Science; 42 Health Sciences; Behavioral and Social Science; Clinical Research; Emerging Infectious Diseases; Coronaviruses; Health Disparities; Infectious Diseases; Rural Health; 1103 Clinical Sciences; 4201 Allied health and rehabilitation science